Contribution of the three-dimensional model to the reliability allocation of multiphase systems", , 2019, :. - S SAADI; M DJEBABRA; O ROUDIES; W BOULAGOUAS (International Journal of Quality & Reliability Management, 2019)
Purpose The purpose of this paper is to deal with the allocation requirements of the dependability of the multiphase systems. Design/methodology/approach It consists of a proposal for a combined methodology based on the simultaneous use of decomposition systems and reliability allocation method. Findings In the developed methodology, the authors use the principles of risk assessment and propose a new formulation of weight allowance with reference to the structural‒functional dependence. Practical implications The suggested methodology provides invaluable help to implementation process analysis. Originality/value The adopted allocation approach is based on the use of a three-dimensional model: temporal, structural and functional decomposition of systems.